IN VITRO ANTI BACTERIAL ACTIVITY OF CLOVE AND PEPPER ON STREPTOCOCCUS MUTANS - V R, SWETA; R V, GEETHA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Dental caries is an oral disease of bacterial origin that causes demineralization and destruction of tooth structure. Streptococcus mutans is Grampositive bacteria that play a vital role in the formation of tooth decay. Instead of opting for synthetic antibacterial substances, natural therapy can be followed. Various spices have bactericidal properties that can be used to prevent tooth decay. Clove is an herb, used as a spice that has effective bactericidal action. Black pepper has been named the black goldâ€ for its wide therapeutic uses. The effect of these spices on Streptococcus mutants is studied using disc diffusion technique. The results obtained from our study shows that the two extracts have got a very good antibacterial activity against S. mutans. Keywords: Bactericidal, Cariogenic, Dental caries, Disc diffusion.